Dovitinib Triggers Apoptosis and Autophagic Cell Death by Targeting SHP-1/p-STAT3 Signaling in Human Breast Cancers. (14th August 2019) - Chiu, Yi-Han; Lee, Yi-Yen; Huang, Kuo-Chin; Liu, Cheng-Chi; Lin, Chen-Si
Abstract : Breast cancer is the most common cancer and the leading cause of cancer deaths in women worldwide. The rising incidence rate and female mortality make it a significant public health concern in recent years. Dovitinib is a novel multitarget receptor tyrosine kinase inhibitor, which has been enrolled in several clinical trials in different cancers. However, its antitumor efficacy has not been well determined in breast cancers. Our results demonstrated that dovitinib showed significant antitumor activity in human breast cancer cell lines with dose- and time-dependent manners. Downregulation of phosphor-( p )-STAT3 and its subsequent effectors Mcl-1 and cyclin D1 was responsible for this drug effect. Ectopic expression of STAT3 rescued the breast cancer cells from cell apoptosis induced by dovitinib. Moreover, SHP-1 inhibitor reversed the downregulation of p -STAT3 induced by dovitinib, indicating that SHP-1 mediated the STAT3 inhibition effect of dovitinib. In addition to apoptosis, we found for the first time that dovitinib also activated autophagy to promote cell death in breast cancer cells. In conclusion, dovitinib induced both apoptosis and autophagy to block the growth of breast cancer cells by regulating the SHP-1-dependent STAT3 inhibition.